(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: Endometriosis is one of the common gynaecological problems mostly affecting the women in reproductive age, associated with non menstrual pelvic pain and other symptoms and recurrence of endometriosis is common after medical or even surgical treatment. Objectives: This review is done to assess, whether conservative surgery and adjunctive hormone suppression therapy is more beneficiary than surgery alone in the treatment of symptomatic endometriosis in term of pelvic pain and disease recurrence. Data sources and search method: Searched had been performed on Cochrane Central Register of Controlled trials, MEDLINE, PsycINFO. Journals and reference lists had been also searched. Review methods: Only Randomized controlled trials were included if they compared the effectiveness of hormone therapy following conservative surgery with surgery alone or surgery plus placebo in the treatment of symptomatic endometriosis. Outcome data had been analysed by using a Mantel-Haenzel Fixed-effect model to perform meta-analysis and results had been presented as Risk ratio for binary data and Standardised Mean difference for continuous data with 95% confidence intervals. Results: Out of 8 trails pelvic pain was reported in 7 trials. No significant benefit was observed both in pelvic pain recurrence (RR= 0.75, 95% Cl- 0.54 to1.04) and disease recurrence (RR 0.89, 95% Cl 0.53 to 1.49) among 5 trials (481& 447 participants) in favour of surgery and adjunctive hormone therapy. On the other hand another 2 trials (280 participants) showed significant benefit in pelvic pain score (Std. Mean difference-0.86, 95%Cl -1.11 to -0.61) but considerable heterogeneity (I²= 95%) was observed. Conclusion: Women who received Post-surgical hormone therapy in the treatment of symptomatic endometriosis had no advantages in respect of endometriosis and pelvic pain recurrence in compared with surgery alone. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17377 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 8-13